Is coracoacromial arch angle a predisposing factor for rotator cuff tears? - Nurdan Çay; Özgür Tosun; Çetin Işık; Özlem Ünal; Merve Gülbiz Kartal; Murat Bozkurt (Diagnostic and Interventional Radiology, 2014)

(untitled)
PURPOSEThe aim of the present study was to investigate whether coracoacromial arch angle is a predisposing factor for rotator cuff tears.METHODSShoulder magnetic resonance imaging (MRI) examinations of 40 patients having shoulder arthroscopy due to rotator cuff tears and 28 patients with normal MRI findings were evaluated retrospectively. Acromio-humeral distance, coraco-humeral distance, the angle between the longitudinal axis of the coracoacromial ligament and longitudinal axis of the acromion (coracoacromial arch angle), and thickness of the coracoacromial ligament were measured.RESULTSIn patients with rotator cuff pathology the mean coraco-humeral distance was 7.88±2.37 mm, the mean acromio-humeral distance was 7.89±2.09 mm, and the mean coracoacromial arch angle was 132.38°±6.52° compared to 11.67±1.86 mm, 11.15±1.84 mm, and 116.95°±7.66° in the control group, respectively (P < 0.001, for all). In regression analysis, all three parameters were found to be significant predictors of rotator cuff tears. The mean thickness of the coracoacromial ligament was not significantly different between the patient and control groups (0.95±0.30 mm vs. 1.00±0.33 mm, P > 0.05).CONCLUSIONAcromio-humeral and coraco-humeral distances are narrower than normal limits in patients with rotator cuff tears. In addition, coracoacromial arch angle may be a predisposing factor for rotator cuff tears.